Dictation: An Effective Way to Enhance Students’ Listening Ability - Atika Salman Paris; Yulandari, Evi Safitri; Rosyidi, Ahmad Zuhri; Suryadi, Hendra (Jurnal Ilmiah Global Education, 2024)
This classroom action research was aimed at improving students’ listening achievement using the dictation method at the seventh graders of MTs Sakinatul Walidain NWDI Boro’ Gerung. The subject of this study consisted of 30 students. This classroom action research consisted of two cycles and four phases, those are planning, acting, observing, and reflecting. The finding of the study indicated that the utilization of the dictation method was significantly effective in improving students’ listening skills. It can be seen from the students’ scores in the pre-cycles and after conducting all the cycles. Thus, it can be concluded that the students’ achievements are improved after conducting the dictation method in the teaching and learning process. Based on the findings of the research, it can be drawn that the use of the dictation method can improve students' listening skills in the narrative text.